Advocating for the Protection of Rights of Children and Women in Nigeria: an Appraisal - Umejiaku , Nneka (Journal of Legal Studies, 2020)
The protection of children and women in Nigeria is very critical because their integration in every sphere is a precedent to the growth and development of nations. However, they face diverse discrimination and violence because they are very vulnerable. The object of this study is to examine the rights of children and women by x-raying the various legal and institutional frameworks that provide for their rights, as well as dangers posed by taking their rights for granted. The work analyses factors that inhibit their protection and proffers a viable solution. In this paper, we adopt the doctrinal and empirical methods of legal research. The study discovers that despite a legion of legislation, children and women are exposed to many factors such as legal, social, economic, and obnoxious cultural practices. Further, the work reveals that inherent lapses are visible in our legal framework particularly the 1999 Constitution (as amended), Child’s Rights Act and other relevant legislation. Accordingly, the work recommends for the eradication of factors that promote child and women abuse and review of relevant laws. The work further recommends for a serious synergy between the government and non-governmental organizations for the protection of children and women.